HUBUNGAN ANTARA PENERIMAAN DIRI DAN FAKTORRESIKO LAINNYA DENGAN TINGKAT DEPRESI PADA REMAJA PENYANDANG CACAT TUBUH DI KABUPATENTANGERANG - Chotijah Auliana Gusti (2019)
Depression ranks fourth place in the world, with the highest prevalence of its sufferers are teenagers. Depressive disorders arise due to various internal factors such as selfacceptance of the disability that they owned or external factors such as others perspective about their existence. Self-acceptance is an ability of an individual to accept their ownself which is characterized by self-confidence and self-esteem. This study aims to determine the correlation between self-acceptance with the level of depression in adolescents with disabilities. This research uses analytic observation method with cross-sectional approach and the sampling method is non-probability sampling with consecutive sampling technique on 75 respondents. The results of the analysis with Chi square statistical tests showed that there was a correlation between self-acceptance with the level of depression in adolescents with disabilities (p = 0,000). The conclusion is that there is a significant relationship between self-acceptance with the level of depression in adolescents with disabilities in Tangerang Regency